Analgesic and Anti-Inflammatory Activity of Pinus roxburghii Sarg. - Dhirender Kaushik; Ajay Kumar; Pawan Kaushik; A. C. Rana (Hindawi Limited, 2012)
The Chir Pine, Pinus roxburghii, named after William Roxburgh, is a pine native to the Himalaya. Pinus roxburghii Sarg. (Pinaceae) is traditionally used for several medicinal purposes in India. As the oil of the plant is extensively used in number of herbal preparation for curing inflammatory disorders, the present study was undertaken to assess analgesic and anti-inflammatory activities of its bark extract. Dried and crushed leaves of Pinus roxburghii Sarg. were defatted with petroleum ether and then extracted with alcohol. The alcoholic extract at the doses of 100 mg/kg, 300 mg/kg, and 500 mg/kg body weight was subjected to evaluation of analgesic and anti-inflammatory activities in experimental animal models. Analgesic activity was evaluated by acetic acid-induced writhing and tail immersion tests in Swiss albino mice; acute and chronic anti-inflammatory activity was evaluated by carrageenan-induced paw oedema and cotton pellet granuloma in Wistar albino rats. Diclofenac sodium and indomethacin were employed as reference drugs for analgesic and anti-inflammatory studies, respectively. In the present study, the alcoholic bark extract of Pinus roxburghii Sarg. demonstrated significant analgesic and anti-inflammatory activities in the tested models.